Turbulent flow simulation based on the IDDES approach using the code zFlare - Troshin, Aleksey Igorevich; Molev, Sergey Sergeyevich; Vlasenko, Vladimir Viktorovich; Mikhaylov, Sergey Vladimirovich; Bakhne, Sergey; Matyash, Sergey Vladimirovich (Computational Continuum Mechanics, 2023)
The experience gained in scale-resolving simulations of turbulent flows using the in-house code zFlare developed at the Central Aerohydrodynamic Institute (TsAGI) is described. The code allows simulating the three-dimensional unsteady flows of arbitrary geometry on the basis of either unsteady Reynolds equations or a hybrid scale-resolving approach. The capabilities of the code zFlare concerning its applicability to the three-dimensional turbulent flows of a single-component gas with a constant heat capacity are discussed. To close the equations of turbulent motion, the following models are used: the Menter turbulence model based on the Boussinesq hypothesis and its analogue for the hybrid scale-resolving approach, and two non-Boussinesq turbulence models: the Cécora et al. model and its original analogue for the hybrid scale-resolving approach. A full description of non-Boussinesq models is provided. The numerical set-up of the test examples of scale-resolving simulations based on the code zFlare is presented: the isotropic turbulence decay; the developed turbulent flow in a plane channel; the turbulent flow in a smooth expanding channel with the boundary layer separation. The first two tests are used to adjust the coefficients of the models for hybrid simulations, and the third one is used to validate these models. The results obtained with the zFlare code (using the hybrid approach and based on the Reynolds equations) are compared with the known reference data for each test case and with the results of simulations by other authors. The test case concerning the subsonic flow in an expanding channel and the boundary layer separation shows that the new non-Boussinesq hybrid scale-resolving method predicts the average velocity field significantly better than the analogous hybrid simulation using the Boussinesq hypothesis-based model.
Keywords: gas dynamics; hybrid simulation methods; URANS; IDDES; TsAGI code zFlare; numerical implementation; verification tests